Judy Moody and the Bad Luck Charm - McDonald, Megan; Reynolds, Peter 1961- (Somerville, Mass. : Candlewick Press, 2012)
Participating in a spelling bee in the hope of winning a trip to Washington, D.C., Judy finds herself depending on her lucky penny while tackling such challenges as a nemesis and a pot-bellied pig.
Keywords: Fate and fatalism -- Fiction; Spelling bees -- Fiction; Family life -- Fiction; School stories